Adapting educational practices for Generation Z: integrating metacognitive strategies and artificial intelligence - Chardonnens, Sarah (Frontiers in Education, 2025)
The educational landscape is evolving rapidly due to the technological transformations brought by the digital age, necessitating innovative approaches to engage Generation Z learners. This study explores the specific educational needs of Generation Z, defined as individuals born between 1997 and 2012, and examines the role of metacognitive strategies and artificial intelligence (AI) in enhancing their learning experiences. A systematic literature review was conducted using academic databases such as Google Scholar, Scopus, and PsycINFO to identify 121 relevant studies published between 2000 and 2024. The review focused on research articles that addressed motivation, engagement, self-regulation, and cognitive processes in digital learning environments. The results reveal that active learning strategies such as project-based learning and formative assessment significantly enhance engagement and autonomy in Generation Z students. Furthermore, the integration of AI technologies provides personalized learning paths and real-time feedback, supporting self-regulated learning. However, over-reliance on AI poses risks to the development of critical thinking and self-regulatory skills. The study concludes by proposing a balanced approach to AI integration, suggesting that it should complement human guidance to foster holistic student development. Future research should explore the long-term effects of AI on cognitive development and the design of inclusive AI tools that cater to diverse learners.